Characteristics of transformative innovation policy and implications for science, technology and innovation policy in Vietnam - Dang Thu Giang; Bui Ngoc Thu Ha (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The world is facing rapidly increasing social challenges and uncertainties that make it difficult for existing views on the goals and tools of science, technology and innovation (STI) policies to address current crises and pose a need for alternatives. In this context, STI policy researchers are increasingly interested in developing a STI policy framework capable of enhancing innovation capacity and cooperation among stakeholders, minimizing socio-technical constraints, promoting resilience and risk prevention, uncertainty and lack of knowledge. This policy framework is called the Transformative Innovation Policy. This article aims to review the existing research on the characteristics of the transformational innovation policy, thereby, drawing some implications for the development STI policy of Vietnam. Code: 22121601